Analysis of the impact of price and brand image on consumer decisions to purchase Baturaja cement products in Palembang City - R. A. Firy Yuandita; Marlina Widiyanti; Aslamia Rosa; Ahmad Maulana (International Journal Labs, 2025)
The Indonesian Cement Association (ASI) projects growth for cement companies in 2022, but challenges persist, including declining demand and overcapacity in the national cement industry, leading to intensified price competition. This research was conducted with the aim of determining the influence of price and brand image on consumer purchasing decisions for Baturaja cement products in the city of Palembang, offering valuable insights into consumer behavior within the cement market. The study employed a quantitative approach, specifically utilizing multiple linear regression analysis to determine the influences of price, brand image, and purchasing decisions. The results show that price has a positive and significant effect on consumers' purchasing decisions in buying Baturaja cement products. Brand image is a significant influencer on consumer decisions.